Optimizing Household Energy Consumption Using Numerical Approaches to Reduce Costs and Environmental Impacts - Saluky; Fathimah , Aisya (Etunas, 2023)
In an effort to face the challenges of increasing global energy consumption and its environmental impacts, optimizing energy use in the household sector is one of the important solutions. This article proposes a numerical approach to optimize household energy consumption with the aim of reducing costs and environmental impacts. Through mathematical modeling and simulation, this method evaluates the energy use of household electrical devices, and analyzes efficient energy consumption patterns. The results of the study show that the implementation of this optimization strategy can reduce energy costs by up to 20% and reduce carbon emissions, thus supporting environmental sustainability. This approach can be applied by both urban and suburban households, making a significant contribution to green energy initiatives and national energy-saving policies.